2019
DOI: 10.1186/s12199-019-0793-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between incidence of fatal intracerebral hemorrhagic stroke and fine particulate air pollution

Abstract: Objective Few studies investigating associations between fine particulate air pollution and hemorrhagic stroke have considered subtypes. Additionally, less is known about the modification of such association by factors measured at the individual level. We aimed to investigate the risk of fatal intracerebral hemorrhage (ICH) incidence in case of PM 2.5 (particles ≤ 2.5 μm in aerodynamic diameter) exposure. Methods Data on incidence of fatal ICH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…This may increase the number of patients with these conditions in the future. In addition, further attention should be paid to the relationship between other diseases and chemicals in the air, not just "SBS" and "MCS" [38][39][40]. Analysis using individual characteristics as adjustment variables (model 1) revealed the significant association between the pre-SBS group and a history of "allergic rhinitis," a history of "mental illness," and the presence or absence of an "interest in air quality and odor."…”
Section: Discussionmentioning
confidence: 99%
“…This may increase the number of patients with these conditions in the future. In addition, further attention should be paid to the relationship between other diseases and chemicals in the air, not just "SBS" and "MCS" [38][39][40]. Analysis using individual characteristics as adjustment variables (model 1) revealed the significant association between the pre-SBS group and a history of "allergic rhinitis," a history of "mental illness," and the presence or absence of an "interest in air quality and odor."…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, results from the Women’s Health Initiative, a large prospective study from the US, displayed that short-term exposure to PM2.5, PM10, NO 2 , NO x , SO 2 , and O 3 was not associated with risk of total stroke, ischemic stroke, or specific etiologies of ischemic stroke, whereas NO 2 (odds ratio (OR) 1.24, 95% CI 1.01–1.52 per interquartile range (IQR) increase) and NO x (OR 1.18, 95% CI 1.03–1.34) were associated with increased risk of hemorrhagic stroke in post-menopausal women [ 53 ]. The role of short-term PM2.5 concentrations for fatal hemorrhagic stroke was examined in a Chinese study showing that risk was particularly pronounced in subjects with diabetes mellitus (OR 1.26, 95% CI 1.09–1.46), emphasizing that subjects with preexisting disease conditions may be more susceptible to the adverse effects of air pollution [ 54 ]. A summary of the association between air pollution and cerebrovascular disease (mostly stroke) is provided in Figure 4 , presenting the relative risk for the development of cerebrovascular disease in association with air pollution by country [ 55 ].…”
Section: Evidence From Human and Animal Studiesmentioning
confidence: 99%
“…Many articles reported relationship between long-term exposure to PM 2.5 and increased risks of incident stroke (Atkinson et al 2013 ; Lipsett et al 2011 ; Ljungman et al 2019 ; Lin et al 2016 ; Korek et al 2015 ; Hoffmann et al 2015 ; Dirgawati et al 2019 ) and ischemic heart disease (Carey et al 2016 ; Hartiala et al 2016 ; Katsoulis et al 2014 ; Loop et al 2018 ; Ueda et al 2012 ; Villeneuve et al 2015 ; Stockfelt et al 2017 ). A case-control study (Qian et al 2019 ) reported that fatal intracranial hemorrhage incidence was associated with PM 2.5 exposure and diabetes might increase the risk for intracerebral hemorrhage incidence in relation to PM 2.5 . In this meta-analysis, we found the evidence that exposure to different levels of ambient PM 2.5 per unit was related to risk of HS in cohort studies.…”
Section: Discussionmentioning
confidence: 99%